2014
DOI: 10.1002/adem.201300488
|View full text |Cite
|
Sign up to set email alerts
|

Martensitic Phase Transformation and Deformation Behavior of Fe–Mn–C–Al Twinning‐Induced Plasticity Steel during High‐Pressure Torsion

Abstract: The transformation between the face centered cubic austenitic and hexagonal close-packed martensitic phases during high-pressure torsion processing was observed in a Fe-Mn-C-Al twinning-induced plasticity steel. This phase transformation was not found in the same material processed by unidirectional compressive and tensile deformation. Initiated by the high-pressure loading, the martensite phase initially increased with torsional strain but diminished subsequently. Texture evolution of the austenitic phase was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…A similar trend was also reported in an AISI 304L steel which was cold rolled to form α' phase and then processed by HPT where an ε phase was developed [20]. An ε phase was also reported after HPT processing of an Fe-Mn-C-Al steel but it was formed from austenite in the very early stage of HPT [19].…”
Section: Stabilization Of the ε Phase By Hptsupporting
confidence: 59%
See 2 more Smart Citations
“…A similar trend was also reported in an AISI 304L steel which was cold rolled to form α' phase and then processed by HPT where an ε phase was developed [20]. An ε phase was also reported after HPT processing of an Fe-Mn-C-Al steel but it was formed from austenite in the very early stage of HPT [19].…”
Section: Stabilization Of the ε Phase By Hptsupporting
confidence: 59%
“…Specifically, it was reported that ε hexagonal martensite was formed when the processing was carried out at -196 ºC while only austenite was observed when processing the material at room temperature [15]. It was also reported that the ε martensite formed in an Fe-Mn-C-Al steel processed by HPT from the austenite phase [19]. Finally, it was also reported that a cold rolled 304L stainless steel with an α' martensite microstructure developed ε martensite in HPT processing and the amount of the ε martensite increased with increasing strain and applied pressure [20].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the present study, we investigate the influence of pressure on the formation of the ductile β-phase in γ-based TiAl alloys, which is not only of fundamental interest, but is also most relevant to modelling high-pressure deformation techniques, such as high-pressure torsion, in order to achieve severe plastic deformation [11][12][13][14][15] and high-pressure near-net-shape forging [16][17][18][19]. These deformation processes operate at pressures up to 7 GPa and forces exceeding 1 GN, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…As a metastable phase, the FCC phase will induce martensitic transformation when subjected to an external load, and the phase transformation can induce plasticity, which is a TRIP effect [13,18]. While maintaining the TRIP effect, twinninginduced plasticity of high-manganese steel will occur, due to the higher Mn content, which is a TWIP effect [8,[19][20][21][22]. The experimental results show that the tensile strength reaches 900 MPa and ductility is increased by about 60% compared with high-strength steel.…”
Section: Introductionmentioning
confidence: 99%